Tahajud Prayer as a Spiritual Intervention in Coping with Stress among Final-Year Students - Fajar, Muhammad; Syahputra, Afit; Kamil, Muflichan; Lubis, Apdi (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the role of Tahajud prayer as a form of spiritual intervention in helping final-year students cope with stress during their academic journey, particularly in the stages of thesis writing and graduation preparation. The research method employed is a quantitative approach with a correlational design. Data were collected through questionnaires measuring the frequency of performing Tahajud prayer and students’ coping stress levels. The findings revealed a significant relationship between the consistency of performing Tahajud prayer and students’ ability to manage academic stress. These results highlight that Tahajud prayer not only serves as a voluntary act of worship but also contributes positively to strengthening spirituality, enhancing inner peace, and improving emotional regulation among students. This research is expected to provide new insights into the role of worship in developing coping strategies, especially for final-year students.